2018
DOI: 10.1007/s00262-018-2264-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of myeloid regulatory cells (MRCs) in maintaining tissue homeostasis and promoting tolerance in autoimmunity, inflammatory disease and transplantation

Abstract: Myeloid cells play a pivotal role in regulating innate and adaptive immune responses. In inflammation, autoimmunity, and after transplantation, myeloid cells have contrasting roles: on the one hand they initiate the immune response, promoting activation and expansion of effector T-cells, and on the other, they counter-regulate inflammation, maintain tissue homeostasis, and promote tolerance. The latter activities are mediated by several myeloid cells including polymorphonuclear neutrophils, macrophages, myeloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 61 publications
(82 reference statements)
2
62
0
Order By: Relevance
“…The immunosuppression present in the SIRS/CARS states, e.g., in sepsis and many autoimmune diseases, can increase the risk for persistent infections and multiple organ failure. However, not only severe insults but all chronic inflammatory disorders can provoke an immunosuppressive condition which counteracts the pro-inflammatory responses, thus alleviating the destructive effects of persistent inflammation [4,111,126]. Many pathological conditions involving chronic inflammation display both pro-inflammatory and anti-inflammatory characteristics, i.e., they create a local SIRS/CARS state.…”
Section: Inflamed Microenvironment Provokes Immunosuppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunosuppression present in the SIRS/CARS states, e.g., in sepsis and many autoimmune diseases, can increase the risk for persistent infections and multiple organ failure. However, not only severe insults but all chronic inflammatory disorders can provoke an immunosuppressive condition which counteracts the pro-inflammatory responses, thus alleviating the destructive effects of persistent inflammation [4,111,126]. Many pathological conditions involving chronic inflammation display both pro-inflammatory and anti-inflammatory characteristics, i.e., they create a local SIRS/CARS state.…”
Section: Inflamed Microenvironment Provokes Immunosuppressionmentioning
confidence: 99%
“…Recently, it has been observed that both myeloid and lymphoid cells are able to exhibit extensive plasticity; for instance many immune cells display both the pro-inflammatory and anti-inflammatory phenotypes in a context-dependent manner, e.g., after infiltration of these cells into stressed tissues. The immune suppressive phenotypes are commonly called regulatory subtypes since they can inhibit the functions of immune effector cells [4,5]. The best characterized immunosuppressive subtypes of myeloid cells include immature myeloidderived suppressor cells (MDSC) as well as regulatory macrophages (Mreg/M2c) and dendritic cells (DCreg/ tolDC).…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the biology of tolDC and the development of protocols for the generation of tolDC in vitro , opened the possibility to translate their use as immunotherapy in clinical trials for immune-mediated diseases ( 115 , 116 ). These therapies are not simple alternatives to Treg-based therapies, but they are complementary.…”
Section: Cell-based Approachesmentioning
confidence: 99%
“…A number of studies have demonstrated that MDSCs support tumor progression and metastasis in the development of tumor‐associated immunosuppressive microenvironment . More recently, MDSCs have been reported to accumulate and expand in infectious disease conditions, such as trauma, burns, and inflammation . In particular, MDSCs were found to be dramatically increased in number, which remained elevated in the spleen, lymph nodes and bone marrow during polymicrobial sepsis, which contributes to sepsis‐induced T‐cell suppression and preferential polarization of T‐helper 2 cells .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 More recently, MDSCs have been reported to accumulate and expand in infectious disease conditions, such as trauma, burns, and inflammation. 8,9 In particular, MDSCs were found to be dramatically increased in number, which remained elevated in the spleen, lymph nodes and bone marrow during polymicrobial sepsis, which contributes to sepsis-induced T-cell suppression and preferential polarization of T-helper 2 cells. 10 In a recent study, it was shown that the number of circulating MDSCs is persistently increased in sepsis patients and associated with adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%